2017
DOI: 10.3389/fpls.2017.01780
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CRISPR/Cas9 Genome Editing of Phytoene desaturase in Cassava

Abstract: CRISPR/Cas9 has become a powerful genome-editing tool for introducing genetic changes into crop species. In order to develop capacity for CRISPR/Cas9 technology in the tropical staple cassava (Manihot esculenta), the Phytoene desaturase (MePDS) gene was targeted in two cultivars using constructs carrying gRNAs targeting two sequences within MePDS exon 13. After Agrobacterium-mediated delivery of CRISPR/Cas9 reagents into cassava cells, both constructs induced visible albino phenotypes within cotyledon-stage so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 35 publications
4
143
0
1
Order By: Relevance
“…Integrating CRISPR/Cas9 constructs into the cassava genome proved to be efficient for achieving gene editing as 91% of transformed lines carried INDELs at the target sites, and desired homozygous and bi‐allelic mutations were observed in 78% of plant lines. These frequencies compare favourably to previous CRISPR/Cas9‐mediated mutagenesis studies in cassava, rice and tomato (Ma et al ., ; Odipio et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Integrating CRISPR/Cas9 constructs into the cassava genome proved to be efficient for achieving gene editing as 91% of transformed lines carried INDELs at the target sites, and desired homozygous and bi‐allelic mutations were observed in 78% of plant lines. These frequencies compare favourably to previous CRISPR/Cas9‐mediated mutagenesis studies in cassava, rice and tomato (Ma et al ., ; Odipio et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the low incidence of the latter in plants, identical NHEJ repair may be more likely (Peng et al, 2016). While transgenic plants derived from FECs are thought to be of single cell origin ( Figure S3), reducing the likelihood of transgenic chimeras (Schreuder et al, 2001;Taylor et al, 1996), Odipio et al (2017) have reported the production of chimeric plants via CRISPR/Cas9-mediated gene editing of phytoene desaturase in cassava. Complex genotypes were not characterized in depth, but they are likely chimeras resulting from Cas9/ sgRNA activity being delayed until after embryogenic units began to replicate (Odipio et al, 2017;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other starches (e.g., from maize and potato), pure-white cassava starch contains low levels of fat (0.08-1.54%), proteins (0.03-0.6%), and phosphorus (0.75-4%), making it an excellent starch resource for various industrial applications (Richard et al, 1991;Moorthy, 2002;Balagopalan, 2002;Sharma et al, 2016). Modified starches of cassava have been broadly used in the food, textile, Wang et al, 2014;Bredeson et al, 2016) and development of cassava transformation technology (Liu et al, 2011;Zhang et al, 2017), we now have the capacity to breed novel cassava cultivars with desirable traits using state-of-the-art technologies including CRISPR/Cas9-based genome editing (Odipio et al, 2017;Sun et al, 2017;Bull et al, 2018;Gomez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%